(untitled) (The Peerian Journal, 2025)
The research aims to determine the readiness of technical and administrative personnel at Rafidain and Rasheed Banks in the event of a sudden cyber attack. The study’s problem was the main challenges resulting from rapid changes in the field of financial technology and the risks associated with its use. Banks’ reliance on digital technologies in their operations may open the door to the emergence of multiple risks. The importance of the study lies in identifying the extent of the contribution of banking management in confronting the electronic banking risks that occur suddenly in AL-raafidayn and Al-Rasheed Banks. The study used the descriptive analytical approach. To achieve this, a questionnaire was designed for all employees of the departments working in the Iraqi banks (Rafidain - Rashid) in Baghdad Governorate, which specialize in the nature of their work in managing electronic banking risks. Rafidain and Rashid banks have effective operating systems capable of managing electronic banking risks. However, there is a noticeable weakness in the availability of virus software. The study emphasized the importance of increasing periodic testing of computer operating systems to avoid electronic banking risks